USING OF PhET–INTERACTIVE SIMULATION IN TEACHING OF GENERAL CHEMISTRY TO PHARMACEUTICAL STUDENTS IN HIGHER EDUCATION ESTABLISHMENT - Okrepka, Halyna (Educological discourse, 2020)
The problems and prospects of using virtual simulators for increasing the interactivity of educational materials in teaching general and inorganic chemistry in higher educational institutions are considered. The virtual practical works in general chemistry with the use of PhET’s simulations by pharmacist students were tested in accordance with the developed protocols and instructions. The advantages and disadvantages of the virtual practical works on the PhET–Interactive Simulation (http://phet.colorado.edu) are formulated. Performing practical tasks on the PhET simulators enhances the quality of knowledge. It is established that the use of PhET simulations is an effective method of interactive learning, which helps to improve the learning of material in both traditional lectures and demonstrations, as well as in practical classes. Students have a growing cognitive interest in real experiment, developing research and experimental competencies, in particular, the ability to formulate and ask questions, make predictions, use evidence to support ideas, focus on the main details, choose the optimal algorithms for the experiment, develop facility with commonly-used scientific representations and measurement tools, coordinate across scientific representations, science models, and real world situations. Students study to identify cause-effect relationships, make connections to everyday life. PhET simulations provide students with the opportunity to work with new material and develop further interest in science, however, the effectiveness of learning depends not only on the PhET, but also on whom and where it is used, how it is integrated into the learning process. PhET–-Interactive Simulations are effective for students to develop the skills and competencies needed to master the following chemical disciplines.